Need Analysis of A Metacognitive-Oriented ESP Module Design for Tourism Village Guides in the Riau Islands Province - Maldin, Siska Amelia (Universitas Pahlawan Tuanku Tambusai, 2026)
Tourism village guides play a strategic role in representing local identity and facilitating cross-cultural communication; however, many experience difficulties in using English effectively and regulating their own learning. This study aims to identify the linguistic, metacognitive, and motivational needs underlying the design of a metacognitive-oriented English for Specific Purposes (ESP) module for tourism village guides in the Riau Islands. Adopting a qualitative needs analysis design, the study involved five tourism village guides selected through purposive sampling. Data were collected using semi-structured interviews and an open-ended ESP needs questionnaire, and analyzed through thematic analysis to identify patterns related to target situation needs and learning needs. The findings indicate that speaking skills dominate professional language use, particularly in explaining attractions and interacting with tourists, while challenges persist in spontaneous communication and complaint handling. Additionally, guides demonstrate limited and unsystematic use of metacognitive strategies despite strong professional motivation. The study concludes that integrating contextualized speaking tasks with explicit metacognitive scaffolding is essential for developing a sustainable, learner-centered ESP module for tourism village guides.